Ordered Nanomaterial Thin Films via Supported Anodized Alumina Templates - Es-Souni, Mohammed; Habouti, Salah (Frontiers in Materials, 2014)
Supported anodized alumina template films with highly ordered porosity are best suited for fabricating large-area ordered nanostructures with tunable dimensions and aspect ratios. In this paper, we first discuss important issues for the generation of such templates, including required properties of the Al/Ti/Au/Ti thin-film heterostructure on a substrate for high-quality templates. We then show examples of anisotropic nanostructure films consisting of noble metals using these templates, discuss briefly their optical properties and their applications to molecular detection using surface-enhanced Raman spectroscopy. Finally, we briefly address the possibility to make nanocomposite films, exemplary shown on a plasmonic–thermochromic nanocomposite of VO2-capped Au-nanorods.